THE INFLUENCE OF VOCABULARY, READING HABITS, THE MASTERY OF LANGUAGE STYLE ON WRITING POETRY SKILL - Sahri Ero (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2016)
The purpose of this research is to know direct influence mastery of vocabulary, reading habits, mastery of language styles, on poetry writing skill. This research applied survey method with path analytical technique. Research population was student at the State Senior High School 107 of Jakarta in 2014/2015 academic year. Sample was selected with quota technique. Data collection was done by using questionnaire and test techniques. The result of the research concluded that: (1) there is a direct influence of vocabulary on student’s mastery of language styles with coefficient path score is 0,250 and level of direct influence is 0,466; (2) there is a direct influence of reading habit on students language styles with coefficient path score is 0,437 and level of direct influence is 0,554; (3) there is a direct influence of vocabulary on student’s poetry writing skill with path coefficient score is 0,153 and level og direct influence is 0,548; (4) there is a direct influence of reading habits on mastery of poetry writing skill with path coefficient score is 0,360 and level of direct influence is 0,704; and (5) there is a direct influence of style language on the poetry writing skill, with path coefficient score is 0,496 and level of direct influence is 0,766.